Hajj Travelogues : Texts and Contexts from the 12th Century until 1950 - Leeuwen, Richard van, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2024)
In Hajj Travelogues: Texts and Contexts from the 12th Century until 1950 Richard van Leeuwen maps the corpus of hajj accounts from the Muslim world and Europe. The work outlines the main issues in a field of study which has largely been neglected. A large number of hajj travelogues are described as a textual type integrating religious discourse into the form of the journey. Special attention is given to their intertextual embedding in the broader discursive tradition of the hajj. Since the corpus is seen as dynamic and responsive to historical developments, the texts are situated in their historical context and the subsequent phases of globalisation. It is shown how in travelogues forms of religious subjectivity are constructed and expressed.